2019
DOI: 10.1302/0301-620x.101b5.bjj-2019-0070
|View full text |Cite
|
Sign up to set email alerts
|

Medial malleolar fractures

Abstract: The medial malleolus, once believed to be the primary stabilizer of the ankle, has been the topic of conflicting clinical and biomechanical data for many decades. Despite the relevant surgical anatomy being understood for almost 40 years, the optimal treatment of medial malleolar fractures remains unclear, whether the injury occurs in isolation or as part of an unstable bi- or trimalleolar fracture configuration. Traditional teaching recommends open reduction and fixation of medial malleolar fractures that are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Fourth, the Herscovici classification would be deemed unclassifiable due to the atypical height and direction of fracture lines or comminution of fracture sites 8 . Carter et al 6 . also recognized the limitation of the Herscovici classification and suggested modifying it by considering a lateral X‐ray or CT scan.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Fourth, the Herscovici classification would be deemed unclassifiable due to the atypical height and direction of fracture lines or comminution of fracture sites 8 . Carter et al 6 . also recognized the limitation of the Herscovici classification and suggested modifying it by considering a lateral X‐ray or CT scan.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, the Herscovici classification would be deemed unclassifiable due to the atypical height and direction of fracture lines or comminution of fracture sites. 8 Carter et al 6 also recognized the limitation of the Herscovici classification and suggested modifying it by considering a lateral X-ray or CT scan. We found moderate interobserver (k = 0.46), substantial intraobserver (k = 0.67) reliability, and 71.8% accuracy for the Herscovici classification, as well as substantial interobserver (k = 0.64), intraobserver (k = 0.74) reliability, and 81.4% accuracy for the new classification system.…”
Section: The Reliability and Accuracy Of The Two Classification Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the special anatomy and injury mechanism of the medial malleolus, the fracture of the medial malleolus has a complicated condition, among which the supination-adduction injuries are even more difficult to treat. Low lateral malleolus fracture or lateral collateral ligament injury can result in vertical split fracture of medial malleolus, and compression fracture of the distal medial articular surface of tibia may occur [ 4 , 5 ]. This fracture pattern is relatively rare, accounting for 12.2% to 21.1% of ankle fractures [ 6 ].…”
Section: Introductionmentioning
confidence: 99%